전방 내로 이동한 덱사메타손 삽입물의 임상양상과 위험인자 분석 - 이혁준(Hyuk Jun Lee), 박운철(Un Chul Park), 유형곤(Hyeong Gon Yu), 이은경(Eun Kyoung Lee) (Daihan angwa haghoi jabji, 2020)
목적: 유리체강내 덱사메타손 삽입물(Ozurdex [오저덱스]®; Allergan Inc., Irvine, CA, USA)이 전방 내로 이동한 환자의 임상양상과 위험 인자, 치료 결과에 대해 분석하고자 한다. 대상과 방법: 전방 내로 오저덱스®가 이동한 환자를 대상으로 후향적 의무기록 조사를 시행하였다. 이전 수술 병력과 오저덱스® 이동의 위험 인자에 대해 조사하였고, 치료 방법과 치료 이후 임상 경과에 대해 분석하였다. 결과: 총 1,276건의 오저덱스® 주입술 중, 오저덱스®의 전방 내 이동이 확인된 환자는 총 6명 6안으로 유병률은 0.47%였다. 6안 모두 인공수정체안이었으며, 이전에 유리체절제술의 병력이 있었다. 유리체절제술을 시행 받은 인공수정체안 환자들이 그렇지 않은 환자들에 비해 전방 내 이동 위험이 더 높았다(odds ratio [OR]=19.2, p=0.009). 또한 유리체절제술을 시행 받은 환자 중 섬모체 소대나수정체낭 복합체의 결손이 관찰된 환자들이 그렇지 않은 환자들에 비해 전방 내 이동 위험이 더 높았다(OR=50.2, p<0.001). 6안 중 1안은 오저덱스® 재배치를, 5안은 수술적 제거를 시행하였다. 수술적 치료를 시행한 이후 각막부종이 있던 3안 모두에서 2달 안에 각막부종이 호전되었으나, 이 중 1명에서는 결국 각막내피세포부전으로 진행하였다. 결론: 유리체절제술을 시행 받은 병력과 수정체낭의 결손 또는 섬모체소대의 약화 및 해리가 있는 경우 오저덱스®의 전방 내 이동에 위험 인자가 되며, 이러한 환자들에게는 오저덱스® 주입에 주의가 필요하다. 오저덱스®의 전방 내 이동이 각막부종과 함께 진단될 경우 가능한 한 빨리 수술적 제거를 고려해야 할 것이다. Purpose: To investigate the clinical features, risk factors, and treatment outcomes for anterior chamber migration of an intravitreal dexamethasone implant (Ozurdex®; Allergan Inc., Irvine, CA, USA). Methods: We retrospectively reviewed the medical records of patients who were diagnosed with anterior chamber Ozurdex® migration. Prior surgical histories were obtained and comprehensive ophthalmic examinations were conducted for all eyes. Treatment strategies and outcomes were also analyzed. Results: Among 1,276 intravitreal Ozurdex® injections, anterior migration occurred in six eyes of six patients (0.47%). All six eyes were pseudophakic, and they had undergone prior vitrectomies. The vitrectomized pseudophakic eyes, in contrast to the nonvitrectomized pseudophakic eyes, were significantly associated with an increased risk of anterior chamber migration (odds ratio [OR] = 19.2, p = 0.009). Moreover, the vitrectomized eyes with reduced zonular/capsular bag complex integrity, in contrast to the vitrectomized eyes with intact zonular/capsular bag complex integrity, were significantly associated with an increased risk of anterior chamber migration (OR = 50.2, p < 0.001). All six eyes underwent surgical intervention: one eye with a repositioning procedure, and the other five eyes with surgical removal of the implant. Corneal edema was resolved within two months after surgery; however, one patient eventually developed corneal endothelial dysfunction. Conclusions: Prior vitrectomy and a defective lens capsule or weak zonules/zonular dehiscence are risk factors for anterior chamber Ozurdex® migration; thus, caution is recommended in these patients. Urgent removal of the implant should be considered when anterior migration of the implant is diagnosed with corneal edema. KCI Citation Count: 0